AKUNTABILITAS PENGELOLAAN KEUANGAN MASJID BERDASARKAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NOMOR 109 - Khatimah, Khusnul; Wahyudi, Agus (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2024)
This study aims to find out how the implementation of the statement of Financial Accountung Standars Number 109 regarding accounting for zakat, infak/sedekah at Masjid Al-Mu’min Karang Goreng Sumbawa Regency based on the concept of recognition and measurement, presentation and disclosure. This research is a type of descriptive research with a qualitative approach. Data collection methods used in this study were observation, interviews and documentation. The determination og informants is based on the main taks and functions of the administrators of the Al-Mu’min Mosque Karang Goreng, Sumbawa Regency in the recognizing and measuring, presenting and disclosing zakat, infak/sedekah. Data analisis uses PSAK No.109 both in terms of recognition and measurement presentation, and disclosure. In the application of PSAK number 109 regarding zakat, infak/seekah at the Al-Mu’min Mosque Karang Goreng Sumbawa Regency. According to the concept of recognizing and measuring zakat, it is quite appropriate even though some have not, but in the future it will be adjusted to the concept of recognizing and measuring zakat PSAK 109. As to the presentation is not perfect though already there, as well as the disclosure of which is not in accordance with PSAK 109.